Vibration dependent branching and photoelectron angular distributions observed across the Cooper minimum region of bromobenzene - Powis, Ivan; Patanen, Minna; Antonsson, Egill; Nicolas, Christophe; Miron, Catalin; Holland, David M.P. (American Physical Society, 2017)
Vibrational state-resolved photoelectron anisotropy parameters, beta, for the ~X 2B1, ~B 2B2, and ~C2B1 state ionizations of bromobenzene have been recorded at photon energies ranging from 20.5 to 94 eV, so spanning the region of the expected bromine Cooper minimum (CM). The ~X state displays no CM and its beta value is also independent of vibrational level, in accord with the Franck-Condon Approximation. The ~B and ~ C state beta values display the CM to differing degrees, but both show a vibrational dependence that extends well below the obvious CM dip. Calculations are presented that replicate these observations of Franck-Condon Approximation breakdown spanning an extended photon energy range. This is the first demonstration of such wide-ranging breakdown detected in the beta anisotropy parameter in the absence of any resonance. Measured and calculated vibrational branching ratios for these states are also presented. Although the ~B state branching ratios remain constant, in accord with Franck-Condon expectations, the ~X and (especially) the ~C state ratios display weak, quasi-linear variations across the studied range of photon energy, but with no apparent correlation with the CM position.